2014
DOI: 10.3961/jpmph.2014.47.2.104
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Stroke by Socioeconomic Status, Age, Sex, and Stroke Subtype: A Nationwide Study in Korea

Abstract: ObjectivesTo date, studies have not comprehensively demonstrated the relationship between stroke incidence and socioeconomic status. This study investigated stroke incidence by household income level in conjunction with age, sex, and stroke subtype in Korea.MethodsContributions by the head of household were used as the basis for income levels. Household income levels for 21 766 036 people were classified into 6 groups. The stroke incidences were calculated by household income level, both overall within income … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 24 publications
3
35
1
Order By: Relevance
“…The association was significant in women but not in men, consistent with previous results from the KHANES [30,31]. Similarly, low education level was associated with higher mortality of CVD [11], clinical outcome of myocardial infarction [12,] and stroke [13]. Interestingly, different impacts of SES, particularly low education level on cardiovascular risks, such as DM [14], HTN [15,16], and dyslipidemia [17] in a gender-dependent manner have also been reported in Korean adults.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The association was significant in women but not in men, consistent with previous results from the KHANES [30,31]. Similarly, low education level was associated with higher mortality of CVD [11], clinical outcome of myocardial infarction [12,] and stroke [13]. Interestingly, different impacts of SES, particularly low education level on cardiovascular risks, such as DM [14], HTN [15,16], and dyslipidemia [17] in a gender-dependent manner have also been reported in Korean adults.…”
Section: Discussionsupporting
confidence: 81%
“…They also concluded that higher education may be the best SES predictor of good health. However, emerging evidence has inconsistently reported that low SES including education level is related to poor health outcome including CVD, stroke, T2DM, HTN, and dyslipidemia [11,12,13,14,15,16,17] particularly in Korean population. Several behavioral measures have linked SES to cardiovascular health, include smoking, alcohol behavior, physical activity, and diet [18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies conducted in countries with predominantly private healthcare systems, such as South Korea and the US, have used possession of health insurance as an indicator. 3,4 Many studies from the UK, where last occupation is collected routinely on the registration of death, classify the social status of occupations as a proxy for socio-economic status. 5 Studies from many countries have used area-based measures, which provide an average SES score for small geographic areas, taking into account factors such as average unemployment levels, and average income; the make up of such scores are typically idiosyncratic to individual countries, and depend on the availability of data from national censuses and other sources.…”
Section: Concepts and Definitionsmentioning
confidence: 99%
“…According to the American Heart Association, stroke is a fatal cerebrovascular disease and the leading cause of death and disability in the United States. In Korea, stroke is the second most common cause of death, and in 2014 it accounted for 50.3 deaths per 100 000 people aged over 65 years, according to Statistics Korea [2]. The age-standardized incidence of ischemic stroke in the population of people aged 35–74 years has been increasing annually, and ischemic stroke accounted for 76% of all cases of strokes in 2009, with a 90-day mortality rate of 3–7% [3].…”
Section: Introductionmentioning
confidence: 99%